1999
DOI: 10.1017/s1355838299990118
|View full text |Cite
|
Sign up to set email alerts
|

Inosine and N 1-methylinosine within a synthetic oligomer mimicking the anticodon loop of human tRNAAla are major epitopes for anti-PL-12 myositis autoantibodies

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…by guest www.bloodjournal.org From aminoacyl-tRNA synthetase activity is also known to localize heavily to the microsomal subfraction in both human and mouse cells of hematopoietic origin. 32 In addition, there is extensive information in the literature implicating tRNA synthetases and their associated tRNAs as the autoreactive antigens in a vast array of autoimmune diseases, [33][34][35][36][37][38][39][40][41][42] suggesting preferential access of these molecules to MHC under conditions in which proteolytic damage might occur (ie, in the lysosomally derived compartments of DCs), thereby allowing the presentation of antigenic aminoacyl-tRNA synthetase peptides. Although it is beyond the scope of this manuscript to model the manner by which tRNA synthetases may participate in the comparison of class I and II antigenic peptide sequences, we implicated them mechanistically in this process by experiments using the glycyl-tRNA synthetase inhibitor ethanolamine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…by guest www.bloodjournal.org From aminoacyl-tRNA synthetase activity is also known to localize heavily to the microsomal subfraction in both human and mouse cells of hematopoietic origin. 32 In addition, there is extensive information in the literature implicating tRNA synthetases and their associated tRNAs as the autoreactive antigens in a vast array of autoimmune diseases, [33][34][35][36][37][38][39][40][41][42] suggesting preferential access of these molecules to MHC under conditions in which proteolytic damage might occur (ie, in the lysosomally derived compartments of DCs), thereby allowing the presentation of antigenic aminoacyl-tRNA synthetase peptides. Although it is beyond the scope of this manuscript to model the manner by which tRNA synthetases may participate in the comparison of class I and II antigenic peptide sequences, we implicated them mechanistically in this process by experiments using the glycyl-tRNA synthetase inhibitor ethanolamine.…”
Section: Discussionmentioning
confidence: 99%
“…Both tRNA-synthetases and tRNAs are the major autoantigens of a wide variety of autoimmune diseases including myositis, systemic lupus erythematosus, interstitial lung disease, and rheumatoid arthritis. [33][34][35][36][37][38][39][40][41][42] Moreover, our transcriptome analysis revealed that 8 tRNA-aminoacyl synthetases were differentially regulated among DCs doubly loaded with matched class I and II determinants (data not shown). Partly on the basis of these considerations, we generated the hypothesis that a recognisome might form between MHC class I and MHC class II in the postlysosomal microsome and further hypothesized that sequence comparisons within this recognisome could be mediated by extracytoplasmic tRNAs and/or their associated tRNA synthetases reported by Agris.…”
Section: Glycyl-trna Synthetase Inhibitor Ethanolamine Implicates Amimentioning
confidence: 99%
“…The clone from which this sequence derived was obtained, and additional sequence information for the amino-terminal half of this protein was determined (see Materials and Methods). The resulting sequence revealed an ORF with homology over its entire coding sequence to Drosophila Adat1, which is not surprising considering that tRNA Ala species from B. mori and humans are very similar (6). While this paper was in preparation, Maas et al (28) reported the characterization of the human ADAT1 and showed that this protein deaminates adenosine 37 of human tRNA Ala .…”
Section: Resultsmentioning
confidence: 67%
“…This inosine is subsequently methylated by an as-yet-uncharacterized enzyme (2). Recently, it has been found that inosine at position 34 and methylinosine at position 37 are major epitopes for anti-PL-12 myositis autoantibodies (6). An adenosine deaminase acting on tRNA (ADAT1) catalyzing the site-specific deamination of adenosine at position 37 in yeast tRNA Ala has been cloned and characterized (15).…”
mentioning
confidence: 99%
“…Therefore, detailed characterization via different techniques and toxicological studies of these oligomers by injecting them into the mice are under progress and will be reported later. Scheme 3. Such oligomers have been reported to oftenly form inside the human cells during the abnormal oxidation of parent compounds [40][41][42] and are responsible for various diseases like Alzheimer disease, Down syndrome and Xeroderma pigmentation. Therefore, it is expected that these studies will throw light on the oxidative pathways of Inosine in human system.…”
Section: Redox Mechanismmentioning
confidence: 99%